2021
DOI: 10.1155/2021/2360717
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Bladder Intravesical Chemotherapy with Three Drugs for Preventing Non-Muscle-Invasive Bladder Cancer Recurrence

Abstract: Epirubicin, gemcitabine, and pirarubicin are widely used as first-line drugs for intravesical chemotherapy to prevent tumor recurrence after transurethral bladder tumor resection for non-muscle-invasive bladder cancer (NMIBC). However, which drug is better is less discussed. A total of 335 NMIBC patients administered intravesical chemotherapy underwent transurethral bladder tumor resection (TURBT) in our hospital from October 2015 to October 2019. After TURBT, all the patients received standard intravesical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(26 reference statements)
2
12
0
Order By: Relevance
“…It has been demonstrated that epirubicin and pirarubicin are equally effective in preventing tumor recurrence 23,24 . Moreover, both epirubicin and pirarubicin are anthracyclines and have similar pharmacological effects 25 . In our study, we found that instillation was also not a risk factor for either DFS or CSS.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been demonstrated that epirubicin and pirarubicin are equally effective in preventing tumor recurrence 23,24 . Moreover, both epirubicin and pirarubicin are anthracyclines and have similar pharmacological effects 25 . In our study, we found that instillation was also not a risk factor for either DFS or CSS.…”
Section: Discussionsupporting
confidence: 49%
“… 23 , 24 Moreover, both epirubicin and pirarubicin are anthracyclines and have similar pharmacological effects. 25 In our study, we found that instillation was also not a risk factor for either DFS or CSS. Moreover, instillation was not statistically associated with either DFS or OS in the Kaplan–Meier analysis.…”
Section: Discussionsupporting
confidence: 40%
“…In parallel, some recent studies demonstrated that adjuvant chemotherapy may be beneficial for PSRCC [ 29 , 30 ]. Intravesical chemotherapy has been deemed as the standard treatment option for muscle-invasive bladder cancer patients after receiving TURBT, which could prevent tumor relapse, inhibit tumor growth, and prolong patient survival [ 31 , 32 ]. We suggested that once PSRCC was considered by biopsy, the combination of advanced therapy should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…BC mice were intravesically instilled with 100 μL of PBS containing THP, THP@HS, THP@HPS and THP@CHPS (equivalent to 5 mg kg −1 THP) for 30 min. 31 After clipping the intravesical instillation catheter, the catheter was unclipped and NP suspension was discharged spontaneously. At 24 h post-instillation, the mice were sacrificed, and the major organs (heart, liver, spleen, kidneys and lungs) and bladders were excised for the quantification of fluorescence intensity using a fluorescence imaging system (Tanon 5200 Multi).…”
Section: Methodsmentioning
confidence: 99%